One-month results from a prospective experience on CAS using C-GUARD stent system: the IRONGUARD-2 study. (25th November 2020) - Sirignano, P; Stabile, E; Stabile, E; Mansour, W; Mansour, W; Speziale, F; Speziale, F
Abstract: Objectives: To evaluate 30-day safety and efficacy of dual layered mesh covered carotid stent systems (DLS) for carotid artery stenting (CAS) in the clinical practice. Background: When compared to carotid endarterectomy CAS has been associated to an higher rate of post procedural neurologic events; these could be related to plaque's debris prolapsing through stent's mesh. Consequently, the need for increased plaque coverage has resulted in the development of DLS. Methods: From January 2017 to June 2019 a physician-initiated, prospective, multispecialty, registry enrolled 733 consecutive patients undergoing CAS using the CGuard Embolic Prevention System (EPS) in 20 centres. Primary endpoint was the stroke up to 30 days; secondary endpoints were the technical and procedural success; external carotid artery (ECA) occlusion; in-hospital and 30 days transient ischemic attack (TIA), acute myocardial infarction (AMI) and death rates. Results: Symptoms were present in 131 patients (17.87%). An embolic protection device (EPD) was used in 731 patients (99.72%). Procedural success was 100%, technical success was obtained in all but one patient (99.86%), who died in-hospital due to a haemorrhagic stroke. Six TIAs, 2 minor strokes, and 1 AMI occurred during in-hospital stay, ECA occlusion was evident in 8 patients (1.09%). Between hospital discharge and 30-day, 2 TIAs, 1 minor stroke and 3 AMIs occurred. Therefore, the stroke rate at 30 days was 0.13. Conclusion: This real-world registry suggests that use of CGuard EPS in clinical practice is safe and associated to a minimal occurrence of adverse neurological events up to 30 days follow up. Funding Acknowledgement: Type of funding source: None